The U-shaped association of non-high-density lipoprotein cholesterol with all-cause and cardiovascular mortality in general adult population - Huang, Yu; Yan, Meng Qi; Zhou, Dan; Chen, Chao Lei; Feng, Ying Qing (Frontiers in Cardiovascular Medicine, 2023)
Background Non-high-density lipoprotein cholesterol (non-HDL-C) has been associated with atherosclerosis. However, the association between non-HDL-C and mortality in adult population remains unclear. We intended to investigate the association of non-HDL-C with cardiovascular and all-cause mortality using national representative data. Methods The study included 32,405 participants from the National Health and Nutrition Examination Survey (1999–2014). Mortality outcomes were ascertained by linkage to National Death Index records through December 31, 2015. Multivariable-adjusted Cox regression models were used to evaluate hazard ratio (HR) and 95% confidence interval (CI) of non-HDL-C concentrations in quintiles. Two-piecewise linear regression and restricted cubic spline analyzes were performed to test dose–response associations. Results After a median follow-up of 98.40 months, 2,859 (8.82%) all-cause and 551 (1.70%) cardiovascular deaths occurred. Compared with the highest group, the multivariable-adjusted hazard ratio (HR) of the first quintile for all-cause mortality was 1.53 (95%CI, 1.35–1.74). Higher non-HDL-C above a cutoff value of 4.9 mmol/L was related with cardiovascular mortality (HR = 1.33, 95%CI, 1.13–1.57). A U-shaped relationship between non-HDL-C and all-cause mortality was found in spline analysis with a cutoff value around 4 mmol/L. Similar results in subgroups analyzes were found among male, non-white population, participants who were not taking lipid-lowering drugs, and with body mass index (BMI) <25 kg/m2. Conclusion Our findings suggest a U-shaped association between non-HDL-C and mortality among adult population.